Analisis Sistem Antrean Pelayanan Administrasi Pasien di Klinik dr. Asih Krustiyani, Probolinggo, Jawa Timur - Kharis, Selly Anastassia Amellia (Jurnal Matematika, 2023)
The discussion taken in this research is "How is the queue system for patient administration services at the Dr. Asih Krustiyani clinic in Probolinggo City". The purpose of this research is to determine the patient queue administration service system at dr. Asih Krustiyani Probolinggo. From the results of the calculation of the performance analysis of the queuing system using the Single Change Single Phase (M/M/1) method. On Mondays, the most patients who come, the highest average is at 19.00 - 20.00 WIB, where the average time required for patients to wait the longest in the queue is 0.09 minutes and the shortest time is 20.00 - 21.00 WIB for 0, 04 minutes. The longest time required by the patient on the system is 0.14 minutes, namely at 19.00 – 20.00 WIB and the shortest time is 0.1 minutes, which is at 18.00 – 19.00 WIB. And 0.061 minutes per patient for the longest waiting time in line with a single server.fluctuated with greater amplitude.